Defect chemistry in 2D materials for electrocatalysis. (June 2019) - Sun, Tao; Zhang, Guoqiang; Xu, Dong; Lian, Xu; Li, Hexing; Chen, Wei; Su, Chenliang
Abstract: Two-dimensional (2D) nanomaterials, including metal-free (graphene, carbon nitride, and black phosphorus et al.) and transition metal-based materials (dichalcogenides, oxides, hydroxides, phosphides, and MXenes et al.), have emerged as promising candidates for electrocatalysis due to their unique physical, chemical, and electronic properties. Specifically, 2D materials with ultra-thin thickness usually possess more vacancy-type defects and exposed edges than bulk materials, resulting in different electronic characteristics relative to those of bulk materials and leading to changes in the reactant absorption energy on catalysts. Introducing heteroatom dopants can further alter the charge distribution in 2D materials, thereby facilitating the formation of new defects and catalytic active-sites to improve the electrocatalytic performance. This review highlights recent defect chemistry advances and developments in 2D materials for electrocatalysis. We discuss various defects in 2D materials, such as edge defects, topological defects and vacancy defects so on, and the effects of defects on electrocatalytic performance. Defect engineering and rational design strategies for controlling defects on 2D materials will also be systematically discussed. Finally, various advanced characterization technologies to reveal different types of defects will be discussed. Graphical abstract: Image 1 Highlights: Defect chemistry advances in 2D electrocatalysts have been systematically summarized. The correlation between the defect chemistry of 2D materials and their catalytic behaviour is well estimated. Defect-engineering approaches and advanced characterizations of nanostructural defects as well as in-situ technologies are presented. The perspectives in 2D electrocatalysts are provided.